Rodinný dům - Dyntarová, Aneta (Vysoké učení technické v Brně. Fakulta stavební, 2024)
Předmětem této bakalářské práce je zpracování projektové dokumentace na úrovni provádění stavby. Cílem práce bylo navrhnout rodinný dům s téměř nulovou spotřebou energie. Novostavba byla navržena na rovinném stavebním pozemku na okraji města Mlázovice. Rodinný dům je dvoupodlažní s částečným podsklepením a je koncipován pro bydlení čtyřčlenou rodinu. Obytná část objektu je zastřešena sedlovou střechou s krytinou z keramických tašek. Garáž, která je přistavěna na severní straně objektu má vegetační plochou střechu. Hlavní nosný systém je z keramických tvárnic. Obvodové suterénní zdivo je z tvárnic ztraceného bednění. Zateplení objektu je řešeno zateplovacím systémem Etics.

The subject of this bachelor thesis is the preparation of project documentation at the level of construction implementation. The aim was to design a family house with almost zero energy consumption. The new building was designed on a flat building plot on the outskirts of Mlázovice. The family house has two floors with a partial basement and is designed for family of four people. The residential part of the house is roofed with a gable roof with a covering made of ceramic tiles. The garage situated on the north side of the building has a vegetated flat roof. The main load-bearing system is made of ceramic blocks. The perimeter basement masonry is made of lost formwork blocks. Thermal insulation of the building is solved by contact insulation system.
Detached house
Keywords: rodinný dům; krov; plochá střecha; vegetační střecha; porotherm; etics; částečné podsklepení; obytné podkroví; ztracené bednění; family house; truss; flat roof; vegetated roof; porotherm; etics; partial basement; residential attic; lost formwork